The Effect of Leadership Style, Work Discipline and Work Motivation on Employee Performance at the Education and Culture Office of Mentawai Islands District - Motisokhi Hura; Desna Aromatika; Fatia Fatimah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of leadership style, work discipline and work motivation on employee performance at the Education and Culture Office of the Mentawai Islands District. This is motivated by the unstable leadership style in the work environment, employee discipline that is still not high, and work motivation is still low, resulting in the completion of the work not being on target at the Mentawai Islands District of Education and Culture Office. This type of research uses a quantitative approach with multiple linear regression method. Data collection techniques with questionnaires and observations. The respondents of this study were 55 employees of the Department of Education and Culture of the Mentawai Islands District. The sampling method used the total sampling method where the entire population in this study was used as the research sample. Hypothesis testing was calculated using the IBM Statistical Package for Social Science (SPSS) version 24.0 program. From the results of this study, it was found that partially leadership style has a significant effect on employee performance, work discipline has a significant effect on employee performance, work motivation has no significant effect on employee performance and leadership style, work discipline and work motivation simultaneously have a significant effect on employee performance at the Education and Culture Office of the Mentawai Islands District.